Enlarging the Toolbox Against Antimicrobial Resistance: Aptamers and CRISPR-Cas - Pereira, Higor Sette; Tagliaferri, Thaysa Leite; Mendes, Tiago Antônio de Oliveira (Frontiers in Microbiology, 2021)
In the post-genomic era, molecular treatments and diagnostics have been envisioned as powerful techniques to tackle the antimicrobial resistance (AMR) crisis. Among the molecular approaches, aptamers and CRISPR-Cas have gained field due to their practicality, sensibility, and flexibility to interact with a variety of extra and intracellular targets. Those characteristics enabled the development of quick and onsite diagnostic tools as well as alternative treatments for pan-resistant bacterial infections. Even with such potential, more studies are necessary to pave the way for their successful use against AMR. In this review, we highlight those two robust techniques and encourage researchers to refine them towards AMR. Also, we describe how aptamers and CRISPR-Cas can work together with the current diagnostic and treatment toolbox.